„Eloquentia sacra”, czyli retoryka w służbie kaznodziejstwa (analiza rękopiśmiennego kompendium retorycznego anonimowego autora reformackiego z XVIII wieku) - Kuran, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The article refers 18th manuscript compendium of rhetoric. Author was a member of the Order of the Reformati. He probably was a lector (i. e. teacher of rhetoric in the monastic college). The manuscript is the proof of the outstanding knowledge of the rhetorical theory. This lecture was intended for future preachers. The whole is subordinated this aim. The material is divided into three parts: De partibus concionis (concerns inventio), De proprietatibus concionis (concerns eloqutio) and De speciebus concionis (describes the types of sermons: doctrinal, ethical, dogmatic, panegyrical and funeral).